The Burning Maze - Riordan, Rick (London, England Puffin, 2018)
The Greek god Apollo is still in the persona of ungifted human teenager Lester Papadopoulos. Now Lester and his demigod friends must go through the Labyrinth to find the third emperor-- and an Oracle who speaks in word puzzles-- somewhere in the American Southwest. But the longer he stays mortal, the weaker he grows... and the less confident that he will be able to regain his place on Mount Olympus.
Keywords: Apollo -- (Deity) -- Juvenile fiction -- Gods, Greek -- Juvenile fiction